2013
DOI: 10.1080/09593330.2013.863952
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of phenol via wet-air oxidation over CuO/CeO2–ZrO2nanocatalyst synthesized employing ultrasound energy: physicochemical characterization and catalytic performance

Abstract: Catalytic wet air oxidation (CWAO) of phenol was carried out under atmospheric pressure of oxygen at 160 degrees C in a stirred batch reactor over copper catalysts supported by CeO2-ZrO2. The copper with different loadings were impregnated over the composite support by a sonication process. The catalysts were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray analysis (EDX), Brunauer-Emmett-Teller (BET) specific surface area and Fourier-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…In the case of MnO x /Ce 0.65 Zr 0.35 O 2 , while the high conversion of phenol (94%) was obtained, phenol was mainly converted to carbonaceous deposits on the surface of the catalyst, which caused the deactivation. The high activity for the CuO supported on CeO 2 -ZrO 2 was also reported by Parvas et al (2014b), while Ni/CeO 2 -ZrO 2 showed low activity (Parvas et al, 2014a). …”
Section: Catalytic Liquid-phase Oxidation Of Phenolsupporting
confidence: 73%
“…In the case of MnO x /Ce 0.65 Zr 0.35 O 2 , while the high conversion of phenol (94%) was obtained, phenol was mainly converted to carbonaceous deposits on the surface of the catalyst, which caused the deactivation. The high activity for the CuO supported on CeO 2 -ZrO 2 was also reported by Parvas et al (2014b), while Ni/CeO 2 -ZrO 2 showed low activity (Parvas et al, 2014a). …”
Section: Catalytic Liquid-phase Oxidation Of Phenolsupporting
confidence: 73%
“…A comparison between FTIR spectra of these samples reveals no noticeable changes. However, the stretching vibration for structural -OH and absorbed water at wave number of 3450 and 1640 cm À1 for all the samples were noticed these vibrations refer to physically absorbed water on all samples after catalyst heat treatment [52][53][54]. The main characteristic bands of clinoptilolite were found at wavelength of 460, 600, 725, and 1075 cm À1 .…”
Section: Edx Analysismentioning
confidence: 89%
“…The peak observed at 2360 cm À1 may be 538 attributed to the asymmetric stretching frequency [y(CO)] of CO 2 539 [66][67][68]. It is caused due to the aerial CO 2 [64].…”
Section: Ftir Analysismentioning
confidence: 91%